Bacteriological profile and antibiotic sensitivity patterns of blood cultures - Reddy, K. Ashwin; Kanth, S. Uday (International Journal of Contemporary Pediatrics, 2016)
Background:Neonatal septicemia is a significant cause of morbidity and mortality worldwide especially so in developing countries. To reduce the mortality caused by neonatal septicemia, it became vital to diagnose it as soon as possible and treat with administration of appropriate antibiotics. The objective of the study was bacteriological spectrum in blood culture of neonates admitted in a hospital, and antibiotic susceptibility pattern of blood culture positive isolates. Methods: A total of 593 blood culture sample were received from NICU admissions for a period of 15 months were included for this study. Under aseptic precautions, 1 ml of blood was collected from a peripheral vein and inoculated into a bottle of Brain Heart Infusion broth and was incubated for 7 days. Repeated sub-culturing was done as per standard procedures. Inoculation on blood agar and Mac-Conkey’s agar plates were made. Any growth was subjected for identification by appropriate biochemical tests. Antibiotic susceptibility testing was done by disc diffusion method. Results:Of the 593 cases studied 12.14 % were blood culture positive. Among the blood culture positive neonates 67% were male neonates. Late onset septicemia (87.5%) was more common than early onset septicemia (12.5%). Gram negative organisms 46 (63.88%) were predominant than gram positive organisms 18 (25%). Klebsiella pneumonia 18 (25%), Citrobacter 10 (13.88%), and Pseudomonas auroginosa was found in 7 (9.72%). The other organisms isolated were Escherichia coli 06 (8.33%), Enterobacter 04 (5.55%), Gram positive organisms were obtained in 18 (25.00%) out of 72 cases. MSSA 06 (8.33%), Enterococci 06 (8.33%) was the commonest organisms isolated. Most of the isolates were more susceptible imipenem, meropenem, and ciprofloxacin to amikacin antibiotics. Conclusions:Blood culture remains the gold standard for the diagnosis of neonatal septicemia. Periodic surveillance of organisms and their antibiotic sensitivity patterns are essential to understand and to prevent emergence of resistant organisms. Effective/Correct selection of antibiotic is essential to decrease mortality and morbidity in the vulnerable group of neonatal population.